2018
DOI: 10.20944/preprints201808.0151.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating Knowledge and Assessment-Centered Reflective-Based Learning Approaches

Abstract: This paper addresses the development of knowledge and assessment-centered learning approaches within a reflective learning framework in a first year physics class in a university faculty. The quality of students’ reflections was scored using a Self-reporting Reflective Learning Appraisal Questionnaire at the end of each learning approach. The results showed the differences between the approaches based on reflections on the learning control through self-knowledge, by connecting experience and knowledg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 47 publications
1
40
0
1
Order By: Relevance
“…Therefore, Higher Education Institutions should transfer sustainability competences to the teaching profession by developing curricula competences in education for sustainability, linking sustainability to both student learning and in-practice teaching [2,5]. It entails promoting student interaction and fostering relationships in socialization and learning [7][8][9]. Education for Sustainable Development is directed towards promoting the development of critical thinking, strategic action, and interpersonal relationships The basic characteristics and conditions for cooperative learning were defined by Johnson and Johnson [8].…”
Section: Students' Cooperative Learning and Sustainable Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, Higher Education Institutions should transfer sustainability competences to the teaching profession by developing curricula competences in education for sustainability, linking sustainability to both student learning and in-practice teaching [2,5]. It entails promoting student interaction and fostering relationships in socialization and learning [7][8][9]. Education for Sustainable Development is directed towards promoting the development of critical thinking, strategic action, and interpersonal relationships The basic characteristics and conditions for cooperative learning were defined by Johnson and Johnson [8].…”
Section: Students' Cooperative Learning and Sustainable Developmentmentioning
confidence: 99%
“…But, their emerging identities as reflective practitioners and adaptive experts should further be enriched and extended through reflective thinking and engagements [20]. Therefore, reflection after the action (on-action) is needed to gradually broaden and deepen a primarily descriptive reflective narrative [9][10][11][12].…”
Section: Students' Identity Construction and Sustainable Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…From the point of view of professional practice, there is a need to break the perpetuation of established teaching practises that are insufficient for developing sustainability competences, and encourage competences related to building capacity for making change in different dimensions. However, in the study by Cebrian and Junyent [72] that is related to competences for ESD, the authors found that student teachers felt more secure in the process of acquiring the knowledge and practical skills related to nature and natural sciences than learning how to guide their future primary school students in the process of developing ethical values, managing their emotions and developing a positive relationship towards sustainability.…”
Section: Competence-oriented Learning In the Teacher Training Programmentioning
confidence: 98%
“…For this purpose, several theoretical frameworks addressed specifically to teacher training have been developed in different universities. Two examples are the KOM-BiNE competency model [71] and the 'Professional Competencies in Education for Sustainability' model [72] -both of them include affective and interpersonal domains and offer different contexts to promote action, reflections and critical thinking, and envisioning future and different scenarios, among other competences.…”
Section: Case Descriptionmentioning
confidence: 99%